Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1017/s1743921305009555
|View full text |Cite
|
Sign up to set email alerts
|

The enigma of lithium in roAp stars

Abstract: Abstract. An internacional project "Lithium in magnetic Ap stars" has been run since 1996 with the purpose of creating an observational database allowing systematic studies of the abnormal occurence of lithium on the surface of cool Ap stars. The 2.6 m telescope at the Crimean Astrophysical Observatory, the ESO CAT, ESO 1.52 m telescope with FEROS, the Nordic Optical Telescope, and the 74" telescope at Mount Stromlo were employed to collect observations at the regions of the lithium resonance lines λ 6103 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 4 publications
(6 reference statements)
2
13
0
Order By: Relevance
“…We find that T eff = 7650 ± 150 K provides a satisfactory fit to the hydrogen Hα and Hβ line wings. This effective temperature is slightly lower than, but nevertheless consistent with, the T eff = 7750 K adopted in other spectroscopic analyses of HR 3831 (Polosukhina et al 2000). The effective temperature of the star was determined using the phase-averaged profiles of the hydrogen lines.…”
Section: Fundamental Stellar Parameterssupporting
confidence: 81%
See 3 more Smart Citations
“…We find that T eff = 7650 ± 150 K provides a satisfactory fit to the hydrogen Hα and Hβ line wings. This effective temperature is slightly lower than, but nevertheless consistent with, the T eff = 7750 K adopted in other spectroscopic analyses of HR 3831 (Polosukhina et al 2000). The effective temperature of the star was determined using the phase-averaged profiles of the hydrogen lines.…”
Section: Fundamental Stellar Parameterssupporting
confidence: 81%
“…The results of our Doppler reconstruction of the lithium abundance map -the first Doppler mapping of this element for a peculiar A star -are presented in Fig. 7 and generally confirm the Li map inferred by Polosukhina et al (2000). Moreover, a more detailed nature of our analysis and, possibly, accounting for variable blending with the Pr  6706.70 Å line yielded a higher contrast abundance map showing some deviations from a strictly axisymmetric distribution, as the shapes of the Li spots close to the positive and negative magnetic poles appear to be somewhat different.…”
Section: Light Elementssupporting
confidence: 81%
See 2 more Smart Citations
“…North et al (1998) found evidence for Li-rich spots on the surface of the rapidlyoscillating Ap star HD 83368. A detailed study by Polosukhina et al (1999Polosukhina et al ( , 2000 revealed a very strong Li i λ6708 line with significant variations in the intensity and position with rotational phase. The behavior of this line was explained by the existence of two opposite Li-rich spots on the stellar surface using the oblique rotator model.…”
Section: Introductionmentioning
confidence: 99%